Between remembrance technology and the production of truth: memory and narrative in asylum politics - Elisa Mencacci (University of Bologna, 2015)
In the institutional pathway for recognition of asylum right, the narrative becomes, according to current regulations, the element to be sieved in order to ascertain title to international protection. The aim of this essay is analyzing the various declensions assumed by the narrative in this institutional process. Weaving together clinical and ethnographic data, drawn from the main phases that foreigners have to pass through in this event, I would like to highlight how, in the asylum system, the narrative takes the value of a tool directed, first of all at checking the applicant's past, and second at co-producing a subject fitting to the media and legal dominant imaginary features. In this specific context, the treatment of traumatic injuries, recognized as basis of interrupted narratives, emerges as issue played in its turn on a double register: as adherence to specific schemes of "therapeutic governance" and as further control of specific events, experienced by asylum seekers in the past.